2019
DOI: 10.18632/aging.101874
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-derived miR-34a increases with age in circulating extracellular vesicles and induces senescence of bone marrow stem cells

Abstract: Extracellular vesicles (EVs) are known to play important roles in cell-cell communication. Here we investigated the role of muscle-derived EVs and their microRNAs in the loss of bone stem cell populations with age. Aging in male and female C57BL6 mice was associated with a significant increase in expression of the senescence-associated microRNA miR-34a-5p (miR-34a) in skeletal muscle and in serum –derived EVs. Muscle-derived, alpha-sarcoglycan positive, EVs isolated from serum samples also showed a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 57 publications
6
106
0
Order By: Relevance
“…For instance, EVs‐miR‐133b and EVs‐miR‐181a‐5p were observed to be significantly up‐regulated after exercise, which possibly may be related to muscle remodelling and homeostasis . Recently, it has been discovered that muscle‐derived EVs carrying senescence‐associated miRNAs, such as miR‐34a‐5p (miR‐34a), were able to induce cellular senescence in bone stem cells . Exosomes belong to EVs and carry significant information, such as proteins, DNAs, miRNAs, and circular RNAs .…”
Section: The Exosome Perspectivementioning
confidence: 99%
“…For instance, EVs‐miR‐133b and EVs‐miR‐181a‐5p were observed to be significantly up‐regulated after exercise, which possibly may be related to muscle remodelling and homeostasis . Recently, it has been discovered that muscle‐derived EVs carrying senescence‐associated miRNAs, such as miR‐34a‐5p (miR‐34a), were able to induce cellular senescence in bone stem cells . Exosomes belong to EVs and carry significant information, such as proteins, DNAs, miRNAs, and circular RNAs .…”
Section: The Exosome Perspectivementioning
confidence: 99%
“…As mentioned above, Fulzele, S. et al. found EVs-derived miR-34a could regulate muscle metabolism ( Fulzele et al., 2019 ). Many studies investigated that physical exercise, which is closely related with muscle regeneration, can induce rapid release of EVs into the blood circulation.…”
Section: Drug Delivery System For Ageing Skeletal Muscle Regenerationmentioning
confidence: 96%
“…Zanotti S et al found that EVs derived from local fibroblasts in the Duchenne muscular dystrophy (DMD) muscle are able to induce a transfer of unactivated fibroblasts to myofibroblasts thereby motivating the fibrotic response (Zanotti et al, 2018). As mentioned above, Fulzele, S. et al found EVs-derived miR-34a could regulate muscle metabolism (Fulzele et al, 2019). Many studies investigated that physical exercise, which is closely related with muscle regeneration, can induce rapid release of EVs into the blood circulation.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
See 1 more Smart Citation
“…The important role played by EVs in cell-cell communication was involved in the loss of bone stem cell population with age. In particular, skeletal muscle EVs carrying senescence-associated miRNAs (miR-34a) can affect BM-MSC viability, decrease Sirt-1 expression and induce BM-MSC senescence, thus suggesting a role of skeletal muscle in age-related decline of BM-MSCs [177]. Conversely, aged MSCs, showing activated AKT signalling which affects EV RNA profile, produce EVs able to cause aging of HSCs [96].…”
Section: Sasp: In Vitro Datamentioning
confidence: 99%